2022
DOI: 10.1038/s41467-022-33199-8
|View full text |Cite
|
Sign up to set email alerts
|

A unifying mechanism for cation effect modulating C1 and C2 productions from CO2 electroreduction

Abstract: Electrocatalysis, whose reaction venue locates at the catalyst–electrolyte interface, is controlled by the electron transfer across the electric double layer, envisaging a mechanistic link between the electron transfer rate and the electric double layer structure. A fine example is in the CO2 reduction reaction, of which rate shows a strong dependence on the alkali metal cation (M+) identity, but there is yet to be a unified molecular picture for that. Using quantum-mechanics-based atom-scale simulation, we he… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
70
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(90 citation statements)
references
References 62 publications
(86 reference statements)
6
70
0
1
Order By: Relevance
“…5,6,[25][26][27][29][30][31][32] Other reports have shown that highly concentrated electrolytes promote CO2 reduction because of a larger degree of enhancement from hydroxide promotion or cation induced electric field effects. 15,29,33,34 Recently, the modification of Cu interfaces with molecular additives such as Nalkylamines, amino acids, and polymer films have emerged as viable methods for enhancing the formation of C2 products. 14,[35][36][37][38] It is thought that changes to the double layer structure from increased interfacial alkalinity, H-bonding, or specific adsorption of the additives improved the formation of C2 products.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…5,6,[25][26][27][29][30][31][32] Other reports have shown that highly concentrated electrolytes promote CO2 reduction because of a larger degree of enhancement from hydroxide promotion or cation induced electric field effects. 15,29,33,34 Recently, the modification of Cu interfaces with molecular additives such as Nalkylamines, amino acids, and polymer films have emerged as viable methods for enhancing the formation of C2 products. 14,[35][36][37][38] It is thought that changes to the double layer structure from increased interfacial alkalinity, H-bonding, or specific adsorption of the additives improved the formation of C2 products.…”
mentioning
confidence: 99%
“…3 The use of weakly solvated cations such as Cs + or K + have been show to improve the rate of CO2 reduction to CO, HCOO − , C2H4, and EtOH in comparison to strongly solvated cations such as Li + . 5,6,[25][26][27][28][29] The enhanced reduction of CO2 to both C1 and C2 products on Cu electrodes from cation-induced effects was predominately from increased electric field intensity at the interface which stabilized key reaction intermediates. 5,6,[25][26][27][29][30][31][32] Other reports have shown that highly concentrated electrolytes promote CO2 reduction because of a larger degree of enhancement from hydroxide promotion or cation induced electric field effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our simulations also demonstrate that the complex between partially desolvated K + and CO δ− 2 persists throughout the CO 2 adsorption process in agreement with the cation-coupled ET model. [22,23] To reinforce the conclusion that short-range interactions between cations and intermediate are behind the cation effects, we also evaluated the role of longe-range electrostatics. Specifically, we address the local electric field modulation due to the cation accumulation in outer Helmholtz plane (OHP), which has been proposed as the main mechanism behind cation-enhanced CO 2 RR .…”
Section: Discussionmentioning
confidence: 99%
“…Complementary density functional theory (DFT) simulations [12] explained this through the stabilization of an adsorbed CO − 2 (ads) intermediate by partially desolvated or specifically adsorbed [25] cations with the short-range interaction in agreement with the cation-coupled electron transfer picture. [22,23] In contrast, Gu et al [14] ascribed the high Faradaic efficiency of CO production (∼90%) on gold to electric field modulation induced by hydrated alkali cations. This was interpreted to arise from long-range dipolefield interactions stabilizing the CO 2 (ads) species.…”
Section: Introductionmentioning
confidence: 99%